Synthesis, crystal structure, DFT/HF, Hirshfeld surface, and molecular docking analysis of 4-(tert-butyl)-4-nitro-1,1-biphenyl - Kumari, Neha; Sharma, Ruchika; Yadav, Archana Akaram; Sankpal, Sandeep Ashok; Raj, Jayakumar Mohan; Murugavel, Saminathan; Kant, Rajni (European Journal of Chemistry, 2023)
4-(tert-Butyl)-4-nitro-1,1-biphenyl has been synthesized, and its structure has been characterized by using some spectroscopic and single-crystal X-ray diffraction techniques. It crystallizes in a monoclinic crystal system with space group P21/n and unit cell parameters: a = 6.4478(3) Å, b = 9.2477(4) Å, c = 23.4572(9) Å, β = 95.114(4)°, V = 1393.11(10) Å3, Z = 4. The molecular structure has been solved by using the intrinsic phasing method. The crystal structure is stabilized by C-H···O interactions. Computational studies were performed using density functional theory (DFT) and Hartree-Fock (HF) methods. The optimized geometry obtained from DFT and HF in the gas phase was compared with solid-phase experimental data retrieved from single-crystal X-ray diffraction results. Frontier molecular orbitals, such as the HOMO/LUMO energy gap, the molecular electrostatic potential, and Mulliken atomic charges, have been investigated. The HOMO LUMO energy gap of 3.97 eV indicates that the molecule is soft and highly reactive. The Hirshfeld surface analysis and their associated fingerprint plots have been used to quantitatively validate the interactions. Further insilico molecular docking studies have been performed with the molecular target Type-II topoisomerase (PDB ID: 1JIJ) and their results suggest that 4-(tert-butyl)-4-nitro-1,1-biphenyl could be considered an anticancer drug.